Preliminary Results from a Structural Conversion Thinning Trial in Eastern Canada. Issue 5 (23rd June 2020) - Dupont-Leduc, Laurie; Schneider, Robert; Sirois, Luc
Abstract: In 2008, a thinning trial consisting in the removal of competitors around high growth potential stems (crop trees, CTs) was initiated as the first step of a structural conversion to transform even-aged stands into uneven-aged stands. Two intensities of thinning by CT release and thinning from below were tested in white spruce ( Picea glauca [Moench] Voss) plantations and in balsam fir ( Abies balsamea [L.] Mill)—dominated naturally regenerated stands. Unlike thinning from below, which aims to remove poor quality stems to improve the growth of residual trees, thinning by CT release aims to reduce competition between dominant trees. Trees thinned by CT release showed a significantly higher diameter at breast height increment than those in the control plots. CT release did not significantly increase stand structure, nor did it reduce stand growth, which helps to address the concerns of regional forest stakeholders. CT release may offer other benefits in the long term, but subsequent interventions are necessary to evaluate if this treatment meets the desired objectives.